Effects of Bromocriptine on Glucose and Insulin Dynamics in Normal and Insulin Dysregulated Horses - Loos, Caroline M. M.; Urschel, Kristine L.; Vanzant, Eric S.; Oberhaus, Erin L.; Bohannan, Adam D.; Klotz, James L.; McLeod, Kyle R. (Frontiers in Veterinary Science, 2022)
The objectives of the study were to study the effects of the synthetic ergot alkaloid (EA), bromocriptine, on glucose and lipid metabolism in insulin dysregulated (ID, n = 7) and non-ID (n = 8) mares. Horses were individually housed and fed timothy grass hay and 2 daily concentrate meals so that the total diet provided 120 % of daily DE requirements for maintenance. All horses were given intramuscular bromocriptine injections (0.1 mg/kg BW) every 3 days for 14 days. Before and after 14 days of treatment horses underwent a combined glucose-insulin tolerance test (CGIT) to assess insulin sensitivity and a feed challenge (1g starch/kg BW from whole oats) to evaluate postprandial glycemic and insulinemic responses. ID horses had higher basal plasma concentrations of insulin (P=0.01) and triglycerides (P=0.02), and lower concentrations of adiponectin (P=0.05) compared with non-ID horses. The CGIT response curve showed that ID horses had slower glucose clearance rates (P=0.02) resulting in a longer time in positive phase (P=0.03) and had higher insulin concentrations at 75 min (P=0.0002) compared with non-ID horses. Glucose (P=0.02) and insulin (P=0.04) responses to the feeding challenge were lower in non-ID compared to ID horses. Regardless of insulin status, bromocriptine administration increased hay intake (P=0.03) and decreased grain (P<0.0001) and total DE (P=0.0002) intake. Bromocriptine treatment decreased plasma prolactin (P=0.0002) and cholesterol (P=0.10) and increased (P=0.02) adiponectin concentrations in all horses. Moreover, in both groups of horses, bromocriptine decreased glucose clearance rates (P=0.02), increased time in positive phase (P=0.04) of the CGIT and increased insulin concentrations at 75 min (P=0.001). The postprandial glycemic (P=0.01) and insulinemic (P=0.001) response following the oats meal was lower after bromocriptine treatment in all horses. In conclusion, in contrast to data in humans and rodents, bromocriptine treatment reduced insulin sensitivity in all horses, regardless of their insulin status. These results indicate that the physiological effects of EA might be different in horses compared to other species. Moreover, because bromocriptine shares a high degree of homology with natural EA, further investigation is warranted in horses grazing endophyte-infected grasses.